Engaging ECD Educators in Leadership Development: Unfolding the Practice - Sharma, Rati (Journal of Durgalaxmi, 2024)
This research article examines key leadership qualities of Early Childhood Development educators, such as passion, compassion, communication, teamwork, adaptability,problem-solving, organization, advocacy, reflection, innovation, and creativity. These qualities are vital in Early Childhood Education and Care settings, influencing interactions and relationships among children and staff. Studies show that such leadership impacts children’s immediate learning and overall development. Focusing on preschools in urban Kathmandu, Nepal, the study examined the leadership development of ECD educators by exploring their past experiences, current positions, challenges, and transformative changes through participation in leadership programs. Interviewing ECD educators in leadership programs revealed their experiences and transformative impacts. The research also identifies challenges faced by ECD educators in leadership roles. Using a narrative interpretative approach, detailed insights from principals and ECD educators in Lalitpur highlight the importance of ongoing professional development and supportive policies.